Insight Into Granular Flow Dynamics Relying on Basal Stress Measurements: From Experimental Flume Tests. Issue 3 (19th March 2022) - Li, Kun; Wang, Yufeng; Cheng, Qiangong; Lin, Qiwen; Wu, Yue; Long, Yanmei
Abstract: Knowledge on the interactions between granular flows and their boundaries is essential for understanding granular flow dynamics. In this study, a series of experiments designed with different conditions were conducted using a flume configuration to investigate the granular flow behaviors and dynamics by particle image velocimetry analysis and basal normal stress measurements. The results demonstrate that the velocity profiles and depth‐averaged shear rates of the granular flows significantly vary with grain size, but display insignificant changes with flow volume. For granular flows with higher content of coarse particles, high magnitude fluctuating stresses with values much greater than the mean normal stress are observed. The particle agitation of the granular flow, which is quantified by the normalized standard deviation of the fluctuating stress from the mean normal stress, exhibits a positive correlation and a negative correlation with the solid inertial stress and the equivalent friction coefficient, respectively. This indicates that the enhanced particle agitation related to the high magnitude fluctuating stress should contribute to the mobility of the granular flows. The generation of the high magnitude fluctuating stress is attributed to the high‐frequency and intensive particle collisions in grain‐scale, which is mainly determined by grain size. In this study, the increase of flow volume mostly resulted in an increase in the fluctuating stress related to the mean normal stress, which exhibits a minor effect on particle agitation and has no contribution toward the mobility of the granular flows. Plain Language Summary: In nature, several types of geological disasters, including rock avalanches, debris avalanches, and debris flows, propagate as granular flows. Granular flows, mainly composed of discrete particles, not only generate static load on the substrate, but also exhibit dynamic interactions with the substrate. The normal stress exerted by granular flows on the substrate can be divided into a mean component and a fluctuating component, reflecting different physical processes during the motion of granular flows. These processes are important for understanding the dynamics of granular flows, such as long‐runout landslides. Based on the measurement of normal stresses beneath the granular flows, we extracted both of the stress components and investigated their effects on the flow dynamics through experiments. We find that the generation of the high magnitude fluctuating component of the basal normal stress can be related to particle agitation and contributes to the runout of the granular flows. The negative correlation between the particle agitation and equivalent friction coefficient may provide insights into the fluidization‐related mechanisms proposed by previous researchers for the explanation of rock avalanche mobility. Key Points: The equivalent friction coefficients of the granular flows decrease with increasing grain size, but vary insignificantly with flow volume The increase of coarse particle content facilitates the generation of high magnitude fluctuating stress and intensifies particle agitation The intensification of particle agitation related to the high magnitude fluctuating stress can promote the mobility of granular flows